(untitled) (Bioresearch Communications, 2024)
Background: There is a huge gap in mental health support for undergraduate students in Bangladesh as there is a shortage of professionals in Government settings. Therefore, the researchers attempted to explore online mental health support as a viable alternative solution to the problem. Objective: The study explored the online mental health support needs of the undergraduate students of Dhaka University. Methodology: A multi-phasic mixed method design was followed in this study. In phase-1, mental health support needs were explored in two focus group discussions (FGDs). In phase-2 of the study, a website was developed to provide online mental health supports for the undergraduate students of Dhaka University. Through this website (www.amentalhealth.org), undergraduate students of Dhaka University as well as all adolescents of Bangladesh will be benefitted by receiving various professional mental health supports including downloadable pdf files containing psycho educational materials. Participants: A total of 21 undergraduate students (mean age 18.86 years & SD of 0.359 ) from different faculties of Dhaka University, participated in the study. Out of 21 participants, there were 10 females and 11 male undergraduate students from Dhaka University. Findings: Participants voiced their support needs on various life-stresses, mood problems, anger problems, suicidal thoughts and adjustment problems in the University. In phase-2 of the study, a website was developed to provide mental health supports to the undergraduate students of Dhaka University. Conclusion: Through this website (www.amentalhealth.org), undergraduate students of Dhaka University will be benefitted by receiving various professional mental health supports. Use of digital technology to provide mental health support to the undergraduate students would increase the rank of Dhaka University globally. Bioresearch Commu. 11(1): 1764-1768, 2025 (January)